PENGARUH KONVERSI LAHAN PERTANIAN TERHADAP TINGKAT KESEJAHTERAAN PETANI (Kasus di Kecamatan Setu, Kabupaten Bekasi) - Danapriatna, Nana; Panuntun, Yunita Utami (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2013)
This study aims to determine the factors associated with the decision of farmers to convert agricultural land and agricultural land conversion effect on the welfare of farm households. Primary data were obtained through questionnaires to the respondents and in-depth interviews to key informants (PPL Agriculture, village officials and PLKB), while the secondary data obtained from the relevant agencies, both government documents and village leaders and village existing institutions. The respondents were selected purposively as many as 34 respondents in village Lubang Buaya, District Setu. Data were analyzed using SPSS. The statistical test used was a cross-tabulation with chi- square test and Spearman rank correlation test. The results showed that the dominant factor influencing farmers' land conversion is the effect of the frequency of arrival of businessmen and entrepreneurs. The greater area of land conversion, the income of farmers after land conversion becomes less. More and more land is converted, the welfare of farmers has declined